2013
DOI: 10.1002/pc.22714
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of modified biofiller‐polypropylene composites

Abstract: This article reports the mechanical, thermal, and morphological properties of polypropylene (PP)-chicken eggshell (ES) composites. Mechanical properties like tensile strength, tensile modulus, izod impact strength, flexural modulus of PP composites with normal (unmodified) eggshell and chemically treated ES [modified ES (MES) with isophthalic acid] have been investigated. PP-calcium carbonate (CaCO 3 ) composites, at the same filler loadings, were also prepared and used as reference. The results showed that PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The Young's modulus of PP composites containing 40 wt% of treated ES was improved by ~ 200%, whereas the crystallinity of PP composites containing pristine ES powder remained almost unchanged [32]. Kumar et al [33] used isophthalic acid in surface functionalization of ES and reported 3-18% improvement in tensile modulus of the PP composite compared to the one containing pristine ES or mineral-based CaCO 3 . Pimelic acid (PA) has also been used to modify ES powder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Young's modulus of PP composites containing 40 wt% of treated ES was improved by ~ 200%, whereas the crystallinity of PP composites containing pristine ES powder remained almost unchanged [32]. Kumar et al [33] used isophthalic acid in surface functionalization of ES and reported 3-18% improvement in tensile modulus of the PP composite compared to the one containing pristine ES or mineral-based CaCO 3 . Pimelic acid (PA) has also been used to modify ES powder.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that studies in the past have mainly been focused on thermoplastics, and limited reports exist on thermosets and elastomeric composites. In recent studies, some important aspects of surface modification of ES powder towards the elastomeric compounds including NR, SBR, and NBR were discussed [32,33]. Specifically, the effect of surface modification, filler loading, and particle size distribution on the curing and thermo-mechanical properties of NR, SBR, and NBR rubbers containing CaCO 3 and various types of ES have been comprehensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The abundant supply of ES makes it an alternative for mineral-based CaCO 3 (chalk or calcite) in polymer composites. 21 The unique hierarchical structure of ES provides a nano-scale porous and rough texture, which allows for an increased interaction with polymers. 22 However, the most mysterious fact about ES is that porosities formed during incubation period in the structure of ES will remain oen even aer they are triturated; so that, micron-size ES could enhance properties of polymer composites somewhat more than that of nano-sized CaCO 3 .…”
Section: (1%) and Organic Materials (4%)mentioning
confidence: 99%
“…24 Likewise, ES powders bearing isophthalic acid were found to cause 3-18% increase in modulus of PP composites compared to those containing unmodied ES or mineral-based micron-size CaCO 3 . 21 Furthermore, ES functionalization with pimelic acid improves the nucleation of PP, dispersion of ES in the matrix, and impact strength of PP. 25 ES was also applied as modier of elastomers such as natural rubber, acrylonitrile butadiene rubber, styrene-butadiene rubber and epoxidized natural rubber.…”
mentioning
confidence: 99%
“…Polypropylene (PP) is a commodity thermoplastic polymer with a number of useful properties, including low density, chemical resistance, high thermal stability, low cost, high softening point, good processability, and high strength . The addition of clay at very small proportions (less than 10% of weight) enhances mechanical, thermal, and barrier properties dramatically .…”
Section: Introductionmentioning
confidence: 99%